Younger Dryas Cladocera assemblages from two valley mires in central Poland and their potential significance for climate reconstructions - Pawłowski, Dominik (Geologos, 2012)
Two sections of sediment from small oxbow-lake infillings located in different river valleys in central Poland were studied by cladoceran analysis in order to examine the response of aquatic ecosystems to the Younger Dryas. Lithological and geochemical records, as well as chydorid (Chydoridae) ephippia analysis were also used to reconstruct Younger Dryas climate trends. A high concentration of cladocerans, as well as the presence of Cladocera taxa preferring warmer water, was found. It is likely that local processes in the oxbow lakes were important, because the presence of warm-preferring taxa was also related to their habitats and their development. Yet local environmental forces, such as the influence of the rivers, habitat modification, macrophyte abundance, and eutrophication, were not only major factors to affect the Cladocera diversity in the Younger Dryas. The observation of changes in the composition and concentration of Cladocera in oxbow-lake infillings indicates that most of the changes occurred in response to climate changes.